2019
DOI: 10.15627/jd.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving Generated Through Automatic Lighting Control Systems According to the Estimation Method of the Standard EN 15193-1

Abstract: The standard EN 15193-1:2017 "Energy performance of buildings -Energy requirements for lighting" introduced a detailed method to calculate the energy demand for lighting in buildings. The method contains a calculation of the daylight supply, which accounts for the impact of lighting control systems, both daylight-linked and occupancy-based. This paper presents the results of a study carried out to quantify, with respect to a manual on/off switch, the energy savings due to the four typologies of daylight-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…The calculated electricity consumption per square meter of the classroom area and the energy savings potential are presented in Table 1. The results show that the energy saving potential through the implementation of on/off control reached about 28% and this value is similar to the results obtained by Lo Verso and Pellegrino [17]. However, it should be noted that this value is obtainable for a classroom oriented to the south-east.…”
Section: Assessment Of Lighting Energy Savings Potentialsupporting
confidence: 87%
See 1 more Smart Citation
“…The calculated electricity consumption per square meter of the classroom area and the energy savings potential are presented in Table 1. The results show that the energy saving potential through the implementation of on/off control reached about 28% and this value is similar to the results obtained by Lo Verso and Pellegrino [17]. However, it should be noted that this value is obtainable for a classroom oriented to the south-east.…”
Section: Assessment Of Lighting Energy Savings Potentialsupporting
confidence: 87%
“…Various control technologies are developed [16] and their implementation influences the energy saving potential. Lo Verso and Pellegrino [17] have estimated the energy savings considering four strategies of daylight-dependent controls, included in the standard EN 15193-1:2017 [18], as well as occupancy control. They considered classrooms with different daylight availability, window orientation and shading system, located in sites at different latitudes and in different climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of energy saving measures related to artificial lighting in buildings greatly depends on the use of lighting control systems linked to daylight and occupancy. Regarding this topic, it is worth noting the study of Loverso et al [7] who carried out a comparative analysis between the four typologies of lighting control systems defined by the Standard EN 15193-1:20017 [8] for a great number of buildings in public and scholastic sectors, in various European locations, showing the great influence of the lighting control system used on saving energy.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of electricity consumption when using four variants of daylighting control systems, with taking into account the use of standard switches, as well as their combination with automatic presence sensors, presented in [18]. During the study was observed several premises with different: 1-availability of daylight; 2-windows orientation; 3 -system of sunscreen devices, located at sites in different latitudes and climatic conditions, as well as taking into account two types of buildings: offices and educational classes.…”
Section: Calmentioning
confidence: 99%